Arbuscular mycorrhizal pecan seedlings alleviate effect of restricted water supply - Babuin, María Florencia (2016)
Pecan [Carya illinoinensis (Wangenheim) K. Koch] seedlings were inoculated with the arbuscular mycorrhizal (AM) fungus Rhizophagus irregularis to evaluate if these organisms establish a symbiotic association and if such an association exerts an influence on restricted water supply response by the plant. After fungal inoculation, plants were grown in a growth chamber. All plants were effectively mycorrhized, with an average infection of 32% for each root. Mycorrhizal colonization led to increased stem height in pecan plants. On restricted water supply, mycorrhizal pecan seedlings presented a higher number of lateral roots and more stem height and diameter than nonmycorrhizal ones. Besides, nonmycorrhizal plants showed an increase in proline content with regard to mycorrhizal ones. Depending on the results, pecan seedlings can be efficiently colonized with the mycorrhizal fungus R. irregularis, under controlled conditions proposed in this work, whereas the symbiotic association with the fungus mitigates restricted water supply.